Devotion Divine : Bhakti traditions from the regions of India - Eck, D.L.; Mallison, F. (Asian Studies - Book Archive pre-2000, 1991)
Bhakti traditions from the regions of India. Co-edition with École Française d'Extrême Orient/Paris.